BEHAVIORAL ECONOMICS: HOW WELL DO INVESTORS IN SERBIA PREDICT THE STOCK PRICES? - Petronijević, Dora (The European Journal of Applied Economics, 2018)
The main goal of this paper is to investigate whether investors in Serbiacan predict future stock prices. This research has been inspired by a numberof similar researches conducted in other countries. The research hasbeen conducted on two Belgrade Stock Exchange's indexes: BELEX 15(represents the market movement of stock prices) and BELEX Sentiment(represents the aggregate investors’ predictions of future stock pricesbehavior). In methodological sense, this analysis was made by usingVector Auto-regression (VAR) model and Granger causality model. Theresults show that investors in Serbia are not very successful in predictionof future prices. The research also shows that investors have basedtheir expectations on historical prices, which resulted in bad predictions.The results of this research are in cohesion with the previous researchesconducted in other developing, transitional countries.